Sistem Informasi Berita Online Berbasis Web Untuk Penyebaran Informasi Publik dengan Menggunakan Metode SDLC - Janitra, Muhammad Randy; Dimas Febriawan (Journal of Informatics Management and Information Technology, 2025)
This research aims to design and develop a web-based information system that simplifies the process for users to search for and access news content online. The study is motivated by the growing need for public information to be disseminated quickly, accurately, and without restrictions of time or location. The system was developed using the WordPress platform and is presented through a website called Koran Pengawas Korupsi (KPK), designed with a responsive interface, intuitive navigation, and an effective search function. The development process employed the Software Development Life Cycle (SDLC) using an iterative approach, allowing for flexible and incremental system development based on user feedback. Data collection methods included surveys and interviews to better understand user needs and guide the design of relevant features. The resulting website includes functionalities such as news search, categorization, user comments, and an administrative dashboard for content management. Testing results indicate that most users are satisfied with the user interface, search capabilities, and visual layout. However, suggestions for improvement were noted, including better content relevance and further design enhancements. In conclusion, this study contributes to the development of user-friendly and efficient web-based information systems that support effective news dissemination to the public.